Schistosome sex matters: a deep view into gonad-specific and pairing-dependent transcriptomes reveals a complex gender interplay - Lu, Zhigang (Sci Rep, 2016)
As a key event for maintaining life cycles, reproduction is a central part of platyhelminth biology. In case of parasitic platyhelminths, reproductive processes can also contribute to pathology. One representative example is the trematode Schistosoma, which causes schistosomiasis, an infectious disease, whose pathology is associated with egg production. Among the outstanding features of schistosomes is their dioecious lifestyle and the pairing-dependent differentiation of the female gonads which finally leads to egg synthesis. To analyze the reproductive biology of Schistosoma mansoni in-depth we isolated complete ovaries and testes from paired and unpaired schistosomes for comparative RNA-seq analyses. Of >7,000 transcripts found in the gonads, 243 (testes) and 3,600 (ovaries) occurred pairing-dependently. Besides the detection of genes transcribed preferentially or specifically in the gonads of both genders, we uncovered pairing-induced processes within the gonads including stem cell-associated and neural functions. Comparisons to work on neuropeptidergic signaling in planarian showed interesting parallels but also remarkable differences and highlights the importance of the nervous system for flatworm gonad differentiation. Finally, we postulated first functional hints for 235 hypothetical genes. Together, these results elucidate key aspects of flatworm reproductive biology and will be relevant for basic as well as applied, exploitable research aspects.